Structure and dynamics of the active Gs-coupled human secretin receptor - Maoqing Dong (Nature Portfolio, 2020)
The class B secretin GPCR (SecR) has broad physiological effects, with target potential for treatment of metabolic and cardiovascular disease. Here, authors present a cryo-EM structure and biochemical studies of secretin binding to the SecR:Gs complex which show that interactions between peptide and receptor were dynamic.